2022
DOI: 10.1021/acs.jpca.2c01835
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Thermolysis Reaction and Chemiexcitation of Coelenterazine Dioxetanes

Abstract: Coelenterazine and other imidazopyrazinones are important bioluminescent substrates widespread in marine species and can be found in eight phyla of luminescent organisms. Light emission from these systems is caused by the formation and subsequent thermolysis of a dioxetanone intermediate, whose decomposition allows for efficient chemiexcitation to singlet excited states. Interestingly, some studies have also reported the involvement of unexpected dioxetane intermediates in the chemiand bioluminescent reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…According to the S 0 and S 1 PECs and their energy gaps calculated by LR-TDDFT, the authors concluded that the uncatalyzed decomposition of neutral 1,2-dioxetanone leads the S 1 -state product to be more efficient than the ET-catalyzed decomposition of the anionic ones. The main evidence to support this conclusion is that a “large and flat biradical region of degeneracy” was observed in neutral decomposition but was absence in anionic decomposition. These explanations regarding the chemiexcitation were incorrect and misunderstood the CI and chemiexcitation.…”
Section: Conical Intersectionsmentioning
confidence: 91%
See 2 more Smart Citations
“…According to the S 0 and S 1 PECs and their energy gaps calculated by LR-TDDFT, the authors concluded that the uncatalyzed decomposition of neutral 1,2-dioxetanone leads the S 1 -state product to be more efficient than the ET-catalyzed decomposition of the anionic ones. The main evidence to support this conclusion is that a “large and flat biradical region of degeneracy” was observed in neutral decomposition but was absence in anionic decomposition. These explanations regarding the chemiexcitation were incorrect and misunderstood the CI and chemiexcitation.…”
Section: Conical Intersectionsmentioning
confidence: 91%
“…Although the existence and roles of S 0 /S 1 CIs in CL of cyclic peroxides were identified and characterized in some theoretical calculations, there are still some misunderstandings in many theoretical works regarding the chemiexcitation mechanism of cyclic peroxides. In these theoretical studies by DFT and LR-TDDFT, the authors did not calculate the Φ S but simply estimated it by a unique criterionthe “degenerated S 0 and S 1 state” or “S 0 /S 1 energy gaps”.…”
Section: Conical Intersectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…BL is widespread in nature and can be found in organisms as different as fireflies, jellyfishes, bacteria, and fungi, among others [1][2][3][4]. Typically, light emission from CL/BL reactions originates due to the formation of a high-energy peroxide intermediate, which decomposes rather quickly with high exothermicity, which allows for chemiexcitation to excited states [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The thermolysis of the four-membered heterocyclic peroxides, e.g., 1,2-dioxetane, generates electronically excited state carbonyl compounds that emit light to release the excess energy (see Figure ). The enhancement of the quantum yields of singlet and triplet chemiexcitation was achieved experimentally by the methylation of the 1,2-dioxetanes. , The chemiluminescent mechanism has been studied by computing potential energy surface (PESs), locating minima, transition states (TSs), and conical interactions and/or intersystem crossings, and identifying the potential reaction pathways. The dynamical quantities, e.g., dissociation time and branching ratios, however, cannot be analyzed in the context of critical points and PESs. The high demand for the nonadiabatic molecular dynamics (NAMD) methods, in which the nuclear motion is regulated by multiple electronic states, has led to the development of different approaches. As the full quantum-mechanical methods are expensive and limited to a few degrees of freedom, the trajectory surface hopping (TSH) method has emerged as one of the most popular tools for the NAMD simulations, which was used recently to study the chemiluminescent processes for the four-membered heterocyclic peroxides …”
mentioning
confidence: 99%